Cheminformatics-driven discovery of natural isoquinoline alkaloid inhibitors of Beta-secretase I for Alzheimer’s management - Iqra Ahmad; Sara Waheed; Bader S. Alotaibi; Sumra Wajid Abbasi; Muhammad Umer Khan; Faiz Ur Rahman; Hanna Dib; Khaled Fahmi Fawy; Umar Nishan; Abid Ali; Aqal Zaman; Mohibullah Shah (PLoS ONE, 2026)
Alzheimer’s disease (AD) is characterized by the gradual deterioration of cognitive functions, speech impairment, and memory loss. It can potentially be treated by targeting the beta-site amyloid precursor protein cleavage enzyme 1 (BACE1), which plays a key role in amyloid plaque formation, neurofibrillary tangles, and hyperphosphorylated tau protein. Current drugs have limitations in terms of safety, efficacy, and blood-brain barrier permeability. In view of this, this study was designed to determine the potential inhibitors of the BACE1 enzyme by virtual screening using a curated library of 415 natural products including terpenoids, phenolic compounds, and alkaloids from different medicinal plants. Based on the docking score and interaction analysis, 50 compounds were selected for the downstream analysis, such as ligand binding interactions, pharmacokinetics, druglikness and physicochemical parameters. Among the lead compounds, Palmatine (compound 45) and Berberine (compound 49), demonstrated optimal drug-likeness and blood-brain barrier permeability among the top compounds. 2-[(9Z,12Z)-heptadeca-9,12-dienyl]-6-hydroxybenzoic acid (compound 4) was inactive in most toxicity parameters. Pharmacophore analysis revealed that Palmatine and Berberine share similar features with the standard, highlighting their potential as effective compounds. Furthermore, structural chemistry analysis provided insights on their shared isoquinoline alkaloid framework, illustrating their structural similarities. Molecular dynamics simulations confirmed the stability of the Palmatine-BACE1 and Berberine-BACE1 complexes during a 50 ns production run. Overall, these findings highlighted the potential of Palmatine and Berberine as promising candidates for the experimental validation and the development of the drugs for the treatment of AD.